Correlation between satisfactory level and visitors number in Cibodas Botanic Gardens, Indonesia - Imawan Wahyu Hidayat; Winarni Winarni; Dwi Novia Puspitasari (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2022)
The level of service quality delivered to the customers on a tourism business might be represented by a satisfaction index. A higher index means that the service is more satisfying and eventually might attract more customers. However, whether the increasing number of customers always reflect a better service quality? This study was aimed to analyze the level of satisfaction and its correlation to the number of visitors to Cibodas Botanic Gardens. The satisfaction index was analyzed based on nine criteria, complying with the regulation of the Minister of State Apparatus Utilization and Bureaucratic Reform, Republic of Indonesia. The analysis started by distributing the questionnaires, which resulted in 1,321 respondents from 2017 to 2019. The number of visitors was obtained by inventoried the number of the sold tickets monthly. Pearson test (r) was used to examine the correlation between the satisfaction index and the number of visitors, and a t-test to evaluate the level of significance (α = 0.05). The findings showed that the index from 2017 to 2019 was relatively stable: 80.8, 80.15, and 80.93 (scale of 25 to 100), respectively. On the other side, the number of visitors tends to rise each year by 24% to 26% instead. The test showed that the correlation is positive but weak (r = 0.236) with no significance. These results provide an overview description and for operators' consideration to manage the site in their policies. The efforts not only focus on attracting more visitors but also on enhancing the quality of the services.JEL Classification: Z30; Z32; Z38